2004
DOI: 10.1080/j.1440-1665.2004.02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Seclusion in a Psychiatric Acute Inpatient Unit

Abstract: Seclusion remains an important part of psychiatric practice. As expected, the use of seclusion in an adult acute unit reflected indirect measures of illness severity. Its use needs to be carefully reviewed and monitored, representing as it does the greatest restriction on a person's freedom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
3
17
1
Order By: Relevance
“…Studies from psychiatric hospitals in the USA (Swett, 1994) have reported a seclusion rate of 12.7%, while in Australia and New Zealand higher rates have been observed, with 20% and 16% respectively of affected patients in acute psychiatric units (El-Badri & Mellsop, 2002;Tunde-Ayinmode & Little, 2004). Regarding European countries, a study by Kaltiala-Heino et al (2000) in general hospital psychiatric units in Finland reported a lower rate of seclusion: 6.6%.…”
Section: Rates Of Seclusion and Restraint In Different Countries And mentioning
confidence: 87%
See 2 more Smart Citations
“…Studies from psychiatric hospitals in the USA (Swett, 1994) have reported a seclusion rate of 12.7%, while in Australia and New Zealand higher rates have been observed, with 20% and 16% respectively of affected patients in acute psychiatric units (El-Badri & Mellsop, 2002;Tunde-Ayinmode & Little, 2004). Regarding European countries, a study by Kaltiala-Heino et al (2000) in general hospital psychiatric units in Finland reported a lower rate of seclusion: 6.6%.…”
Section: Rates Of Seclusion and Restraint In Different Countries And mentioning
confidence: 87%
“…This fi nding is not supported by Fisher (1994), who suggested that several diagnoses are associated with higher seclusion and restraint rates. Among diagnoses, schizophrenia (Thompson, 1986;El-Badri & Mellsop, 2002;Tunde-Ayinmode et al, 2004;Odawara et al, 2005), bipolar disorder (Thompson, 1986;El-Badri & Mellsop, 2002), organic and substance use-related disorders (Kaltiala-Heino et al, 2000;El-Badri & Mellsop, 2002;Odawara et al, 2005), personality disorders (Tardiff, 1981;Swett, 1994;Salib et al, 1998), and mental retardation (Tardiff, 1981;Thompson, 1986) are the most cited. The reason for the difference in the present study is not known.…”
Section: Correlations Of Coercive Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on the effect of gender vary. Some studies report male gender to be a risk factor [20,22], others report a higher risk for female patients [19], and others find no effect of gender [20,24,25]. The time of day (peak in afternoon and early evening) and season (peak in autumn) are non-patient factors influencing the use of restraint [22].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with findings in the Australian study and that found in the review by Fischer in 1994, who found that the diagnoses associated with higher seclusion rates were psychosis, manic symptoms, character disorders, mental retardation and abnormal EEGs. [7,13] When correlating the reasons for seclusion with diagnosis, CI seemed to be a factor in users being secluded for their own safety as evidenced by schizophrenia, CI and dementia being the most common diagnoses. This is possibly due to the nature of their disability as they are vulnerable and open to abuse by other users in the ward.…”
Section: Discussionmentioning
confidence: 99%